Hepatic inactivation of murine Surf4 results in marked reduction in plasma cholesterol - Tang, Vi T; McCormick, Joseph; Xu, Bolin; Wang, Yawei; Fang, Huan; Wang, Xiao; Siemieniak, David; Khoriaty, Rami; Emmer, Brian T; Chen, Xiao-Wei; Ginsburg, David (eLife, 2022)
PCSK9 negatively regulates low-density lipoprotein receptor (LDLR) abundance on the cell surface, leading to decreased hepatic clearance of LDL particles and increased levels of plasma cholesterol. We previously identified SURF4 as a cargo receptor that facilitates PCSK9 secretion in HEK293T cells (Emmer et al., 2018). Here, we generated hepatic SURF4-deficient mice (Surf4fl/fl Alb-Cre+) to investigate the physiologic role of SURF4 in vivo. Surf4fl/fl Alb-Cre+ mice exhibited normal viability, gross development, and fertility. Plasma PCSK9 levels were reduced by ~60% in Surf4fl/fl Alb-Cre+ mice, with a corresponding ~50% increase in steady state LDLR protein abundance in the liver, consistent with SURF4 functioning as a cargo receptor for PCSK9. Surprisingly, these mice exhibited a marked reduction in plasma cholesterol and triglyceride levels out of proportion to the partial increase in hepatic LDLR abundance. Detailed characterization of lipoprotein metabolism in these mice instead revealed a severe defect in hepatic lipoprotein secretion, consistent with prior reports of SURF4 also promoting the secretion of apolipoprotein B (APOB). Despite a small increase in liver mass and lipid content, histologic evaluation revealed no evidence of steatohepatitis or fibrosis in Surf4fl/fl Alb-Cre+ mice. Acute depletion of hepatic SURF4 by CRISPR/Cas9 or liver-targeted siRNA in adult mice confirms these findings. Together, these data support the physiologic significance of SURF4 in the hepatic secretion of PCSK9 and APOB-containing lipoproteins and its potential as a therapeutic target in atherosclerotic cardiovascular diseases.
Keywords: secretion; SURF4; PCSK9; APOB; cholesterol